METODE PELAKSANAAN PEKERJAAN STRUKTUR BAWAH JEMBATAN CIHIEUM KECAMATAN LEMAHSUGIH KABUPATEN MAJALENGKA - Aditya Rachman, Damas; Hendrayana, Yayat (Universitas Majalengka, 2019)
Bridge abutments connect the deck, or surface of the bridge, to the ground and help support its weight both horizontally and vertically. On short bridges, one abutment is placed at either end of the bridge and connected to the embankment, sometimes including a retaining wall. The choice of abutment depends on the available space, geologic features of the bridge site, and available funding for the project. This Cihieum bridge was built using a composite steel structure with a span of 30 m and a width of 7 m, consisting of 2 abutments. With an implementation time of 150 calendar days.